The Implementation ff National Examination as The Direction of National Education Policy - Firdaos, Rijal; Ahmad, Ahmad (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2018)
This study aims to find out how the implementation of the UN can be used as a continues policy material. This research is a literary research where researchers trace the literature related to the implementation of the UN and the direction of educational policy. The results of this study indicate that the implementation of the UN is still needed but with some notes. All supporting components and instruments must be ready and evenly distributed throughout the districts or cities that deal with the competence of teachers, supporting facilities, and public awareness of the importance of the quality of education. The National Exam encourages all parties to work hard in order to achieve better learning outcomes for learners, in accordance with the competency standards of graduates. UN has become a part of the national policy direction, which gave birth to the National-Standard School Examination, the curriculum changes from KTSP to K13, and the implementation of the Full Day School program as an effort to maximize the potential of learners in school activities.